Clinicomorphological Study Of Ovarian Lesions - Maharjan, Sushna (Journal of Chitwan Medical College, 2014)
This prospective study was conducted at College of Medical Sciences-Teaching Hospital (CMS-TH) during December 2008 to May 2010. One hundred and fifty cases were analyzed. Age of the patients, parity, presenting symptoms, types of surgery, clinical diagnosis and complications were retrieved from case sheets. Surface epithelial tumors were more frequently observed above 30 years of age, (62.07%) cases. During 1st to 3rd decades of life, 62.8% germ cell tumors were seen; and sex cord tumors were seen in age group 41-60 years only. For all age groups, benign tumors were common than malignant tumors. There were 10.7% unmarried patients, 5.33% nulliparous, 35.55% of parity 1 to 2; 4% pregnant and 20 % postmenopausal women. There were 86.67% cases neoplastic, and 13.33% non-neoplastic ovarian lesions; 93.85% benign, 5.38% malignant and 0.77% borderline tumors. Surface epithelial tumors were the most common tumors (53.84%) followed by germ cell tumors (43.85%), constituted 46.7% and 38% among all ovarian lesions. The commonest benign tumors were serous cystadenomas and mature cystic teratomas, constituted 40% cases each. Dysgerminoma was the common malignant neoplasm (2.31%), all were seen in adolescents. Most of the other malignant neoplasms were observed above 40 years of age. Seventy percent (70%) of non-neoplastic lesions were hemorrhagic corpus luteum cysts. The commonest presenting symptom was pain in the lower abdomen (82%) followed by abdominal mass/ or distension (48.7%). Constitutional symptoms were observed in malignant cases only. Grossly, majority of the ovarian lesions were of size ranging 5 to 15 cm; and 89.93% cystic lesions. There were 48.7% lesions in the right ovary and 45.3% in the left ovary; 6% bilateral ovarian lesions, all of which were observed in benign and non-neoplastic lesions. The common complication observed was torsion (6.7%) followed by rupture of the cysts (6%). Journal of Chitwan Medical College 2013; 3(4); 17-24 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9549